Twentieth-century contribution to sea-level rise from uncharted glaciers. (22nd November 2018) - Parkes, David; Marzeion, Ben
Abstract Global-mean sea-level rise (GMSLR) during the twentieth century was primarily caused by glacier and ice-sheet mass loss, thermal expansion of ocean water and changes in terrestrial water storage1 . Whether based on observations2 or results of climate models3, 4, however, the sum of estimates of each of these contributions tends to fall short of the observed GMSLR. Current estimates of the glacier contribution to GMSLR rely on the analysis of glacier inventory data, which are known to undersample the smallest glacier size classes5, 6 . Here we show that from 1901 to 2015, missing and disappeared glaciers produced a sea-level equivalent (SLE) of approximately 16.7 to 48.0 millimetres. Missing glaciers are those small glaciers that we expect to exist today, owing to regional analyses and theoretical scaling relationships, but that are not represented in the inventories. These glaciers contributed approximately 12.3 to 42.7 millimetres to the historical SLE. Additionally, disappeared glaciers (those that existed in 1901 but had melted away by 2015, and that therefore cannot be included in modern global glacier inventories) made an estimated contribution of between 4.4 and 5.3 millimetres. Failure to consider these uncharted glaciers may be an important cause of difficulties in closing the GMSLR budget during the twentieth century: their contribution is on average between 0.17 and 0.53 millimetres of SLE per year, compared to a budget discrepancy of about 0.5 millimetres of GMSLR per year between 1901 and 1990. Although the uncharted glaciers will have a minimal role in sea-level rise in the future, and are less important after 1990, these findings imply that undiscovered physical processes are not required to close the historical sea-level budget. From 1901 to 2015, missing and disappeared glaciers produced a rise in sea level that may enable the historical budget for global-mean sea-level rise to be closed without recourse to an undiscovered physical process.